Rivaroxaban: a novel oral anticoagulant for the prevention and treatment of several thrombosis‐mediated conditions. (23rd May 2013) - Sarich, Troy C.; Peters, Gary; Berkowitz, Scott D.; Misselwitz, Frank; Nessel, Christopher C.; Burton, Paul; Cook‐Bruns, Nancy; Lensing, Anthonie W.A.; Haskell, Lloyd; Perzborn, Elisabeth; Kubitza, Dagmar; Moore, Kenneth T.; et al.
Abstract : The development of rivaroxaban (XARELTO®) is an important new medical advance in the field of oral anticoagulation. Thrombosis‐mediated conditions constitute a major burden for patients, healthcare systems, and society. For more than 60 years, the prevention and treatment of these conditions have been dominated by oral vitamin K antagonists (such as warfarin) and the injectable heparins. Thrombosis can lead to several conditions, including deep vein thrombosis, pulmonary embolism, myocardial infarction, stroke, and/or death. Prevention and treatment of thrombosis with an effective, convenient‐to‐use oral anticoagulant with a favorable safety profile is critical, especially in an aging society in which the risk of thrombosis, and the potential for bleeding complications, is increasing. Rivaroxaban acts to prevent and treat thrombosis by potently inhibiting coagulation Factor Xa in the blood. Factor Xa converts prothrombin to thrombin, which initiates the formation of blood clots by converting fibrinogen to clot‐forming fibrin and leads to platelet activation. After a large and novel clinical development program in over 75, 000 patients to date, rivaroxaban has received approval for multiple indications in the United States, European Union, and other countries worldwide to prevent and treat several thrombosis‐mediated conditions. This review will highlight some of the unique aspects of the rivaroxaban development program.